Mindfulness in Akidah Akhlak Learning: A Systematic Literature Review Strategies for Cultivating High School Students' Spiritual Awareness - Ade Saepuloh (Indonesian Journal of Islamic Education and Learning, 2026)
The learning of Aqidah Akhlak at the senior high school level is not only aimed at improving students’ cognitive understanding of Islamic teachings, but also at fostering spiritual awareness and shaping students’ religious character. However, in practice, the learning process often emphasizes cognitive aspects and provides limited opportunities for reflection and internalization of spiritual values. Therefore, the mindfulness approach is considered to have the potential to support the internalization of spiritual values in Aqidah Akhlak learning. This study aims to analyze the implementation, benefits, and relevance of the mindfulness approach in Aqidah Akhlak learning among senior high school students. This research employs a Systematic Literature Review (SLR) method involving the stages of identification, selection, evaluation, and analysis of relevant scientific articles. The literature search was conducted using the Publish or Perish application with a publication range from 2018 to 2025. Based on the selection process, several articles that met the inclusion criteria were analyzed in depth. The results indicate that the mindfulness approach in Aqidah Akhlak learning provides various benefits, including improving learning concentration, emotional regulation, psychological well-being, and students’ spiritual awareness. Furthermore, the integration of spiritual practices such as dhikr, self-reflection, and muhasabah helps students internalize moral values such as patience, gratitude, trust in God, and responsibility in their daily lives. The findings also suggest that mindfulness is relevant in addressing educational challenges in the digital era that require students to develop emotional regulation and self-awareness. Therefore, mindfulness can serve as an effective pedagogical strategy to support more reflective, meaningful, and character-oriented Aqidah Akhlak learning.